Impact of Demonetisation on Indian Economy (Trinity Journal of Management, IT & Media (TJMITM), 2017)
India has amongst the highest level of currencies in circulation at  12.1% of GDP. Cash on hand is an estimated at around 3.2% of  household assets, higher than investment in equities, or roughly  around $ 220 billion. A significant portion of the household cash  on hand is generated by economic transactions going unreported  to tax authorities earns the name of black money and becomes a  major constituent of parallel economy.. Demonetisation is  considered to be a major step towards eliminating the menace of  black money and cause a debilitating impact on parallel  economy. The present paper endeavors to evaluate both short  run and medium term impact of demonetisation on Indian  economy. The paper elucidates the impact of the move taken by  Government of India on credit availability, spending, level of  activity and government finances.
Keywords: Demonetisation; Black Money; Parallel Economy; Household cash